2018
DOI: 10.1364/oe.26.011321
|View full text |Cite
|
Sign up to set email alerts
|

65 GHz Q-switched mode-locked waveguide lasers based on two-dimensional materials as saturable absorbers

Abstract: Two-dimensional (2D) materials have generated great interest in the past few years opening up a new dimension in the development of optoelectronics and photonics. In this paper, we demonstrate 6.5 GHz fundamentally Q-switched mode-locked lasers with high performances in the femtosecond laser-written waveguide platform by applying graphene, MoS and BiSe as saturable absorbers (SAs). The minimum mode-locked pulse duration was measured to be as short as 26 ps in the case of BiSe SA. The maximum slope efficiency r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…In 2013, the researchers fabricated a graphene SAM and applied it to a single-chip waveguide laser to obtain the modelocked pulses with a pulse width of 1.06 ps and a repetition rate of 1.5 GHz, [575] as shown in Figure 19. Since then, waveguide lasers using layered materials such as graphene, [576][577][578][579][580][581][582][583][584][585] Bi 2 Se 3 , [586,587] TMDCs, [588][589][590][591][592] and BP [593,594] have been further developed, as shown in Table 6. It can be seen that, for Q-switching operation, the minimum pulse width and maximum pulse energy are 25.2 ns [576] and 310 nJ, [579] respectively.…”
Section: Waveguide/disk Lasersmentioning
confidence: 99%
“…In 2013, the researchers fabricated a graphene SAM and applied it to a single-chip waveguide laser to obtain the modelocked pulses with a pulse width of 1.06 ps and a repetition rate of 1.5 GHz, [575] as shown in Figure 19. Since then, waveguide lasers using layered materials such as graphene, [576][577][578][579][580][581][582][583][584][585] Bi 2 Se 3 , [586,587] TMDCs, [588][589][590][591][592] and BP [593,594] have been further developed, as shown in Table 6. It can be seen that, for Q-switching operation, the minimum pulse width and maximum pulse energy are 25.2 ns [576] and 310 nJ, [579] respectively.…”
Section: Waveguide/disk Lasersmentioning
confidence: 99%
“…It was reported that the maximum slope efficiency reached 53% in the case of MoS 2 SA. This is also the first Q-switched mode-lock waveguide laser using MoS 2 and Bi 2 Se 3 SAs in the waveguide platform, which pave the way for the compact ultrafast photonic applications [121].…”
Section: Lasersmentioning
confidence: 98%
“…This fabrication technique also allows arbitrary figures of compact waveguides to be achieved to further integrate with photonic devices. Among various structures, depressed cladding waveguide, featured with ambient low refractive index tracks, stands out for its easy integration with other optoelectronics and better light field confinement [120,121]. For example, Li et al applied ReSe 2 as an SA into a monolithic Nd:YVO 4 waveguide platform (with 50 μm diameters and 11 mm long), as presented in Figure 4A, where the depressed cladding configuration was adopted.…”
Section: Lasersmentioning
confidence: 99%
“…The GHz laser sources have potential applications in areas such as ultrafast optical sampling, frequency combs generation, and high-speed optical communication. [79,83], and achieved 6.5 GHz QML laser on femtosecond-laser-written Nd:YVO 4 waveguide. With different nonlinear optical properties (e.g.…”
Section: Mode-locked Waveguide Lasersmentioning
confidence: 99%